Pengembangan Konten Video Animasi Motion Graphic sebagai Media Promosi Kesehatan Personal Hygiene Menstruasi bagi Remaja Putri - Rona Zulfa Triamanda; Trixie Salawati; Nurina Dyah Larasaty (Universitas Ahmad Dahlan, 2022)
Background: Menstrual personal hygiene is an effort to maintain personal hygiene and reproductive organs during menstruation. If the personal hygiene of menstruation is poor, it may be at risk of infection of the reproductive tract and can cause vaginal discharge. The results of the preliminary study showed that 8 out of 10 adolescents knew little about menstrual hygiene. Purpose: To produce animated video content motion graphics of adolescent girls' about personal hygiene during menstruation. Method: This study using uses the PProcess media development model. The expert review was conducted by media experts and materials experts. The pre-test media will conduct on girls adolescents aged 13-18. Results: The expert review results showed that the animation video media motion graphic about menstrual personal menstrual hygiene belonged to an excellent category (81-100%), and the materials in the animated videos motion graphic about menstrual personal hygiene belonged to a good category (61-80%). The results of a small-scale experiment conducted on 13-18-year-old girls showed an increase in knowledge before and after watching animated videos about menstruation and personal hygiene. All interviewees believed that animated videos were very educational and useful for young women. Conclusion: This study shows a change in the increase in knowledge of adolescent girls after seeing an animated video motion graphic about menstrual personal hygiene.